(untitled) (Materiali di Estetica. Terza serie, 2024)
This article honors the late Eugenio Borgna, a distinguished figure in phenomenological psychiatry, reflecting on his final works In ascolto del silenzio and L’ora che non ha più sorelle. Sul suicidio femminile. Borgna’s writings delve deeply into human emotions and their aesthetic expressions, blending narrative with clinical insight to touch readers personally. The review particularly notes his focus on the poet Antonia Pozzi, underlining his unique approach to exploring the interplay between psychological experience and literary expression.